THE PHENOMENON OF SYNONYMY IN ENGLISH PHILOSOPHICAL TERMS - Boynazarov, Islom (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This article comprehensively discusses the phenomenon of synonymy in philosophical terms, highlighting its importance, problems and opportunities in philosophical discourse. It also discusses the dual nature of synonymy from a linguistic point of view, highlighting its advantages and disadvantages in order to explain the conceptual differences or interrelationships of synonymous terms.